Pengaruh Karakteristik lndividu, Sikap, dan Pelatihan Terhadap Penggunaan Teknologi lnformasi dan Kinerja Pegawai Kelurahan Menuju Terwujudnya E-Government - Karis Widyatmoko; Y. Tyas Gatur Pramudi (JURNAL DIAN, 2011)
The government's use of information technology that is not maximum is caused by human resource problem. lnformation technology infrastructure will not be utilized maximally without good human resource support and this will result ini bad pedormance. Meanwhile there are not many research on human resource in information technolgy. lnformation technology human resource, commonly called as user, can be seen from characteristics, attitude, and training so that the inftuence ofthese variables towards the use of informaton technology needs to be investigated. The empiric data were taken from 105 employees of 21 districts (kelurahan) in Semarang. The data were processed by using SPSS 16. The result shows that the use of lT is significantly influenced by the characterstics, attitude and training, while the use of lT in kelurahan also inftuences thepertormance of employees. Characterisctic has negative influence and it is dominated by age factor. Education and the length of working time do not have significant influence. Affective attitude and psychomotor give positive influence to the use of lT, while cognitive attitude does not. Computer training variable is dominated by duration rather than frequency factor. To improve the use of computer in kelurahan, age, affective attitue, psychomotoric attitude, and the duration of training should be considered. From the processed empiric data, the use of IT significantty influences performance. Therefore, e-government should be implemented since this will influncethe employee perfomance.Keywords: attitude, characteristics, pertormance, the use of computer, training